Pendampingan Penggunaan Biaya Overhead Pabrik Dalam Mengelola Biaya Produksi Di O2 Ice Cream Ice Cream Pematang Siantar - Asyrina Fadilah Chaniago; Joana Ruth Paulin Saragih; Vena Angriva Putri; Dimas Ardiansyah; Elfina Okto Posmaida Damanik (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
This community service activity was carried out by students of the Faculty of Economics, University of Simalungun, Pematang Siantar. The method of this activity is qualitative and goes through several important stages such as, Planning Stage, Training and Mentoring Stage, and Reporting Stage. This activity aims to assist UMKM O2 Ice Cream Pematang Siantar in determining factory overhead costs in managing production costs. The results of this community service activity have effective results and run smoothly when this activity takes place.